High Levels of DEK Autoantibodies in Sera of Patients With Polyarticular Juvenile Idiopathic Arthritis and With Early Disease Flares Following Cessation of Anti–Tumor Necrosis Factor Therapy. Issue 4 (22nd February 2018) - Mor‐Vaknin, Nirit; Rivas, Miguel; Legendre, Maureen; Mohan, Smriti; Yuanfan, Ye; Mau, Theresa; Johnson, Anne; Huang, Bin; Zhao, Lili; Kimura, Yukiko; Spalding, Steven J.; Morris, Paula W.; et al.
Abstract : Objective: The nuclear oncoprotein DEK is an autoantigen associated with juvenile idiopathic arthritis (JIA), especially the oligoarticular subtype. DEK is a secreted chemotactic factor. Abundant levels of DEK and DEK autoantibodies are found in inflamed synovium in JIA. We undertook this study to further characterize the nature of DEK autoantibodies in screening serum samples from 2 different cohorts that consisted mostly of patients with JIA. Methods: DEK autoantibody levels were analyzed in sera from 33 JIA patients, 13 patients with other inflammatory conditions, and 11 healthy controls, as well as in 89 serum samples from JIA patients receiving anti–tumor necrosis factor (anti‐TNF) therapy. Recombinant His‐tagged full‐length DEK protein (1–375 amino acids [aa]) and the 187–375‐aa and 1–350‐aa His‐tagged DEK fragments made in a baculovirus system were used for enzyme‐linked immunosorbent assay (ELISA) and immunoblotting. The C‐terminal 25‐aa fragment of DEK was expressed in a glutathione S‐transferase–tagged vector. ELISA results were calculated as area under the curve by the trapezoidal rule. Results: DEK autoantibody levels were significantly higher in patients with polyarticular JIA than in those with oligoarticular JIA, and were higher in patients with polyarticular JIA who had more active disease after cessation of anti‐TNF therapy. Immunoblotting against the C‐terminal 25‐aa fragment of DEK confirmed that this section of the DEK molecule is the most immunogenic domain. Conclusion: DEK autoantibody levels are higher in patients with polyarticular JIA than in those with oligoarticular JIA, and higher in patients who have disease flares after cessation of anti‐TNF therapy. The C‐terminal 25‐aa fragment is the most immunogenic portion of DEK. These findings are significant with respect to the nature of DEK autoantibodies, their contribution to JIA pathogenesis, and their implications for JIA management.